Perception of Students about E-learning: A Single-center Experience from Saudi Arabia - Hussein Algahtani; Bader Shirah; Ahmad Subahi; Ahmed Aldarmahi; Sabina Nisar Ahmed; Muhammad Anwar Khan (Dr. Sulaiman Al Habib Medical Journal)
Introduction: E-learning is the use of the internet and associated devices for educational purposes without geographical constraints. This study aims to assess the perception of students at King Saud bin Abdulaziz University for Health Sciences in Jeddah, Saudi Arabia, about E-learning as a teaching modality. Methods: This cross-sectional study was conducted between June 2017 and June 2018. The inclusion criteria consisted of healthcare students (medicine, nursing, and college of sciences and health professions). A 40-item closed-ended questionnaire was distributed to the participants and was divided into six main parts: perception, diversity, implications, efficiency, acceptability, and accessibility of E-learning. Results: The response rate was 94.4% (total = 410, retrieved = 387), of which 61.8% (n = 239) stated that they had heard something about E-learning. Meanwhile, 52.2% (n = 202) of students had no idea about virtual patients. Notably, 73.1% (n = 283) agreed that cell phones can be used as a teaching modality, whereas 52.2% (n = 202) opined that cell phones can play a role in stimulating critical thinking among medical students. Sixty percent (n = 232) of students believed that E-learning has the potential to expand educational opportunities. Compared to male students, female students had a higher perception of cheating and fraud (p = 0.039) during E-learning as well as perception of a decline in personal efforts in quest of knowledge (p = 0.032). Conclusion: There is a growing positive perception of E-learning, but the level of acceptance remains low. Further research is required on how to enhance and maximize the confident utilization of ever-increasing opportunities in E-learning. Establishing well-developed E-learning facilities in Saudi educational institutions will tremendously enhance educational opportunities for its students.